ANALISIS YURIDIS PERJANJIAN JUAL BELI PERUMAHAN DENGAN METODE DOWN PAYMENT - Arifin, Arifin; Khasanah, Dian Ratu Ayu Uswatun; Pongantung, Ronald Jolly (Universitas Stikubank, 2025)
Cases of non-performance of contract. on the part of the aggrieved party bring the case to the criminal realm. The charge reported is the fraud article, even though the criminal offense has not been fulfilled. So that it has the potential to cause wrong criminalization, the main problem is the inaccurate use of the fraud article against defaults which are basically civil. The research method uses normative juridical with decision analysis and criminal and civil law studies related to non-performance of contract. and fraud. The results show that non-performance of contract. can only turn into a criminal offense of fraud if there are elements of intent, bad faith, use of deception, or falsification of agreements with the intention of benefiting oneself against the law. Therefore, law enforcement officials should be careful in distinguishing non-performance of contract. and fraud cases to avoid abuse of the law that harms the parties concerned. The hopes and solutions proposed are proportional law enforcement by paying attention to the element of malicious intent in determining criminal offenses, as well as legal education to the public so that they understand the difference between the civil and criminal domains in contractual disputes.